2006
DOI: 10.1002/cne.21080
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular efferent neurons in the optic tectum of rainbow trout

Abstract: The efferent connections and axonal and dendritic morphologies of periventricular neurons were examined in the optic tectum of rainbow trout to classify periventricular efferent neurons in salmonids. Among the target nuclei of tectal efferents, tracer injections to the following four structures labeled periventricular neurons: the area pretectalis pars dorsalis (APd), nucleus pretectalis superficialis pars magnocellularis (PSm), nucleus ventrolateralis of torus semicircularis (TS), and nucleus isthmi (NI). Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 67 publications
(165 reference statements)
5
39
1
Order By: Relevance
“…In a salmonid the preglomerular nuclei have been reported to receive fibers from the optic tectum (Kinoshita et al, 2006) as well as the semicircular torus and to project to the Dm and Dd plus dDl (Folgueira et al, 2005). These connections appear similar to those of the PGlr in cyprinids (Northcutt, 2006;present study).…”
Section: Comparison With Other Teleostsmentioning
confidence: 52%
See 2 more Smart Citations
“…In a salmonid the preglomerular nuclei have been reported to receive fibers from the optic tectum (Kinoshita et al, 2006) as well as the semicircular torus and to project to the Dm and Dd plus dDl (Folgueira et al, 2005). These connections appear similar to those of the PGlr in cyprinids (Northcutt, 2006;present study).…”
Section: Comparison With Other Teleostsmentioning
confidence: 52%
“…Recent studies suggest the presence of tectopreglomerulo-dorsal telencephalic pathways also in salmonids (rainbow trout: Folgueira et al, 2005;Kinoshita et al, 2006). Also importantly, another recent study in goldfish reported that the rostrolateral region of the PGl (PGlr) receives tectal fibers in addition to octavolateral inputs (Northcutt, 2006).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Labeled terminals in the NLVpl were cupshaped and appeared to envelop target neurons in this nucleus (Fig. 4C), a feature shared by afferents to the NLV from various sources (carp: Yoshimoto and Ito, 1993;Ito et al, 1997;Xue et al, 2006b, tilapia: Yang et al, 2004Xue et al, 2005Xue et al, , 2006a; rainbow trout: Kinoshita et al, 2006). Cerebellar injections label this population of granular cells (Fig.…”
Section: Rhombencephalon and Spinal Cordmentioning
confidence: 89%
“…They possessed long apical processes directed toward the pial surface (spv; Fig. 5d-g) and were identified as neurons of type XIV [according to Meek and Nieuwenhuys, 1998;Kinoshita et al, 2006]. The apical processes ramified es- pecially in the stratum album centrale (sac; Fig.…”
Section: Midbrainmentioning
confidence: 99%